2016
DOI: 10.1103/physrevd.93.092006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the top quark mass using charged particles inppcollisions ats=8TeV

Abstract: A novel technique for measuring the mass of the top quark that uses only the kinematic properties of its charged decay products is presented. Top quark pair events with final states with one or two charged leptons and hadronic jets are selected from the data set of 8 TeV proton-proton collisions, corresponding to an integrated luminosity of 19.7 fb −1 . By reconstructing secondary vertices inside the selected jets and computing the invariant mass of the system formed by the secondary vertex and an isolated lep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…[52]). The b-hadron results are consistent with the PYTHIA8 prediction [52], where the uncertainty shown is due to b-quark fragmentation [55,56] (other sources of uncertainty are ignored [52]). The prompt-J=ψ results do PRL 118, 192001 (2017) P…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 69%
“…[52]). The b-hadron results are consistent with the PYTHIA8 prediction [52], where the uncertainty shown is due to b-quark fragmentation [55,56] (other sources of uncertainty are ignored [52]). The prompt-J=ψ results do PRL 118, 192001 (2017) P…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 69%
“…First studies of the fragmentation and hadronization of the b quarks in tt events have been reported in Ref. [2,3]. In this paper, we present the first measurement of the properties of the UE in tt events at a scale Q ≥ 2m t .…”
Section: Introductionmentioning
confidence: 93%
“…A novel technique was presented by the CMS Collaboration in Ref. [97], where m t is measured by exploiting the kinematic properties of final-state charged particles. The observable used in this analysis is the mass m svℓ of the secondary vertex-lepton system, namely the invariant mass of a system made of the charged lepton in W decays and charged hadrons in a jet originating from a common secondary vertex.…”
Section: Final-state Charged Particlesmentioning
confidence: 99%